Геологічні фактори розвитку небезпечних техногенних процесів під час будівництва метрополітену у м. Дніпро - Семенченко, В. О.; Орлінська, О. В.; Пікареня, Д. С. (Національний університет «Львівська політехніка», 2021)
The construction of the first line of the metro led to the development of dangerous engineering and geological processes - suffusion, subsidence, failures and more. This is due to insufficient geological study of future construction. In 2016, the construction of a new metro line began and the development of dangerous man-made processes intensified in the central part of Dnipro. Monitoring and prevention of their manifestation is an urgent task of technogenic security of the city.